Socioeconomic inequity in health care utilization, Iran - Mohammadbeigi, Abolfazl (J Epidemiol Glob Health, 2013)
Reducing poor–rich inequities in health is one of the priorities of both national and international organizations and is also one of the main challenges of health sectors in Iran. Since, in the view of policy making, quantifying the size of inequity in health care utilization (HCU) is a prerequisite for achieving this goal, the current study aimed to determine and compare the socioeconomic inequity in HCU by concentration (C) index and odds ratio (OR). METHODS: A total of 758 households, consisting of 2,131 subjects who were aged 15 or older, were involved in this cross-sectional study, and their data were gathered through interviews. Household economic index (HEI) was created by the factor analysis from the asset data. The C index and OR were used as measures to determine the overall inequity in HCU according to sex (male/female), living area (urban/rural), insurance, and types of HCU (general physician [GP], specialist, and Health Workers [HWs]). RESULTS: The overall rate of HCU was 66.4%. The rates of using GP, specialist care, and HW care were 21.4%, 21.6% and 21.8%, respectively. The overall inequity in HCU was equal to 0.05 (95% confidence interval; −0.069 to 0.165). The C indexes in HCU, according to the subgroups of HCU, were measured as 0.11 (0.09–0.12) for GP, 0.115 (0.01–0.13) for specialist and −0.065 (−0.08 to −0.05) for HWs. Although the rate of utilization increased from poor to rich quintiles, the inequity regarding sex and living area was also low and non-significant. CONCLUSION: People with higher HEI used more specialist and GP care, while people with lower HEI used more HW care. The inequity in HCU was low and non-significant in different quintiles of males, females, urban and rural, as well as those who were insured.